A study relationship between leader behaviors and subordinate job expectancies: A path-goal approach - Sikandar Hayyat Malik (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
This study investigates relationship between leader behavior (directive, supportive, participative and achievement-oriented) of corporate managers and subordinates' job expectancies using House (1974) Path-goal model of leadership. The results reveal that leader behavior affects subordinates' job expectancies. The situational factors (task structure, role ambiguity, stress, need for autonomy, locus of control, need for achievement and perception about abilities) affect subordinates' job expectancies (I&II). While subordinates' attributes/characteristics (age, gender, qualification, rank, experience and length of service under the current supervisor) do not affect job expectancies (I&II) except for rank/position and expectancy-II. Path goal theory predicts that directive leader behavior will be more effective for the subordinates with high need for achievement because directive leader through clarifying path guides subordinates. Similarly, participative leader behavior is also effective as he consults with subordinates in setting, clarifying and achieving goals. The results of this study reveal that there is an inverse relationship between subordinates' job expectancy (I&II). According to Yukl (2006), for subordinates with high need for autonomy, participative leader behavior will increase the intrinsic valence of work
Keywords: 330; Leadership; Subordinates' job expectancies; Path-goal theory; Leader behavior